2010
DOI: 10.1113/expphysiol.2010.055244
|View full text |Cite
|
Sign up to set email alerts
|

Sharpey‐Schafer Lecture: Gas channels

Abstract: The traditional dogma has been that all gases diffuse through all membranes simply by dissolving in the lipid phase of the membrane. Although this mechanism may explain how most gases move through most membranes, it is now clear that some membranes have no demonstrable gas permeability, and that at least two families of membrane proteins, the aquaporins (AQPs) and the Rhesus (Rh) proteins, can each serve as pathways for the diffusion of both CO2 and NH3. The knockout of RhCG in the renal collecting duct leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 121 publications
2
110
1
1
Order By: Relevance
“…Thus it is possible that the approach in the earlier study was not sufficiently sensitive to detect the NH 3 permeability of AQP1. Moreover, at the high level of NH 3 /NH 4 ϩ used in the earlier study, oocytes exhibit large NH 3 /NH 4 ϩ -dependent conductances (24) and substantial decreases in pH i , neither of which appear at the [NH 3 /NH 4 ϩ ] o of 0.5 mM (42,44) used in the present study. Thus it is possible that the data obtained at high [NH 3 /NH 4 ϩ ] o values could reflect oocyte properties and thereby obscure the properties of heterologously expressed AQPs.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 89%
See 2 more Smart Citations
“…Thus it is possible that the approach in the earlier study was not sufficiently sensitive to detect the NH 3 permeability of AQP1. Moreover, at the high level of NH 3 /NH 4 ϩ used in the earlier study, oocytes exhibit large NH 3 /NH 4 ϩ -dependent conductances (24) and substantial decreases in pH i , neither of which appear at the [NH 3 /NH 4 ϩ ] o of 0.5 mM (42,44) used in the present study. Thus it is possible that the data obtained at high [NH 3 /NH 4 ϩ ] o values could reflect oocyte properties and thereby obscure the properties of heterologously expressed AQPs.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 89%
“…Previous work has shown that this aquaglyceroporin conducts water, glycerol, and urea (28). Moreover, as noted in the AQP1 section, other authors, working with 20 mM NH 3 / NH 4 ϩ , have reported that AQP3 conducts NH 3 (24). In the kidney, basolateral AQP3 contributes to water reabsorption along the entire collecting duct (12) and could contribute to urea reabsorption in the inner medullary collecting duct.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 94%
See 1 more Smart Citation
“…CO 2 has a high lipid : water partition coefficient, allowing it to cross the lipid bilayer freely. In addition (although not without controversy [18]), specialized gas channels such as aquaporins (AQP) have been demonstrated to increase membrane permeability to CO 2 [19]. Lactic acid, despite a much lower lipid : water partition coefficient, can cross the membrane as H þ -lactate, translocated by H þ -monocarboxylate transporters (MCT), including MCT1 and the hypoxia-inducible MCT4 [20] (according to the SoLute Carrier family naming convention, SLC16A1 and SLC16A3, respectively).…”
Section: Production and Venting Of Metabolic Acidsmentioning
confidence: 99%
“…2 RhAG may function as an ammonium transporter and/or a gas channel. [3][4][5] When expressed in Xenopus laevis oocytes, the human wild-type RhAG induces a monovalent cation leak considerably enhanced when mutated RhAG transporters are expressed instead. 2 Among membrane abnormalities, OHSt RBCs display a sharp reduction or an absence of stomatin, 6 an integral RBC membrane protein.…”
Section: Introductionmentioning
confidence: 99%